A Time-Truncated Life Test Approach on the new Two-sided Group Chain Sampling Plan with Log-logistic Distribution - Muhammad Farouk; Nazrina Aziz; Zakiyah Zain (International Journal of Supply Chain Management, 2019)
The established new two-sided complete group chain sampling plan (NTSCoGCh), which operates with five acceptance criteria, and the two-sided group chain sampling plan (TS-GCh), which operates with three acceptance criteria, are consumer- and producer-focused plans respectively. Since the number of acceptance criteria influences the responding probability of lot acceptance in lot inspection, this paper suggests the balanced approach of the new two-sided group chain sampling plan (NTSGCh) which operates with four acceptance criteria. The lifetime distribution of Log-logistic is used in this study, and the method of time truncated life test simulation is conducted. The findings proved that the NTSGCh performed better than the NTSCoGCh. Therefore, the NTSGCh is a worthy option for implementation in lot inspection in the manufacturing industry.